Modified Ghost Fluid Method as Applied to Fluid-Plate Interaction (Advances in Applied Mathematics and Mechanics, 2014)
The modified ghost fluid method (MGFM) provides a robust andefficient interface treatment for various multi-medium flowsimulations and some particular fluid-structure interaction (FSI)simulations. However, this methodology for one specific class of FSIproblems, where the structure is plate, remains to be developed.This work is devoted to extending the MGFM to treat compressiblefluid coupled with a thin elastic plate. In order to take into accountthe influence of simultaneous interaction at the interface, afluid-plate coupling system is constructed at each time step andsolved approximately to predict the interfacial states. Then,ghost fluid states and plate load can be defined by utilizingthe obtained interfacial states. A type of acceleration strategy inthe coupling process is presented to pursue higher efficiency.Several one-dimensional examples are used to highlight the utilityof this method over loosely-coupled method and validate theacceleration techniques. Especially, this method is applied tocompute the underwater explosions (UNDEX) near thin elastic plates.Evolution of strong shock impacting on the thin elastic plate anddynamic response of the plate are investigated. Numerical resultsdisclose that this methodology for treatment of the fluid-platecoupling indeed works conveniently and accurately for differentstructural flexibilities and is capable of efficiently simulatingthe processes of UNDEX with the employment of the accelerationstrategy.